Penerimaan Auditor atas Dysfunctional Audit Behavior: Sebuah Pendekatan Karakteristik Personal Auditor - Evanauli, Ratna Prasetyoningrum; Nazaruddin, Ietje (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
This study is aimed at finding out the relationship between personal characteristics and dysfunctional audit behavior. The inconsistency results of previous studies about factors that lead to dysfunctional audit behavior make it necessary to do another research on this matter. This research is important because of the increasing demand from financial statement’s users on auditor professionalism in order to obtain a qualified audit report and dysfunctional audit behavior is one that threatens the quality of audit. The respondents in this study are auditors working at audit firms in Yogyakarta and Surakarta. The sample taken using convenience sampling technique. The hypotheses were examined by using SPSS 16.0 program. The results find that locus of control, performance, and religiosity are significantly influental on dysfunctional audit behavior where as turnover intention has no influence on dysfunctional audit behavior because p value (0,695) α (0,05).